2022
DOI: 10.3389/fimmu.2022.1010932
|View full text |Cite
|
Sign up to set email alerts
|

A one-year unisexual Schistosoma mansoni infection causes pathologic organ alterations and persistent non-polarized T cell-mediated inflammation in mice

Abstract: In exhibiting gonochorism and phenotypic sexual dimorphism, Schistosoma spp. are unique among trematodes. Only females mating with male schistosomes can produce the highly immunogenic parasite eggs which determine the clinical picture of the disease schistosomiasis. The strong immune-modulatory effect of the eggs masks the influence of the adult worms. To shed light on the complexity of the immune response triggered by adult worms of Schistosoma mansoni, we performed a long-term unisexual infection experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…Throughout infection we have shown only minor differences in immune response between female and male single-sex infection with schistosomes. This finding is in line with the initial immunological analysis we have performed on the separate controlled human infection studies( 3, 5 ), as well as a recent murine study which found no immunological differences in chronic male or female single-sex infection( 48 ). However, it is still surprising in the context of prior papers that have shown sex-related differences in immune priming, as well as the known morphological and transcriptional differences between male and female worms ( 4952 ).…”
Section: Discussionsupporting
confidence: 88%
“…Throughout infection we have shown only minor differences in immune response between female and male single-sex infection with schistosomes. This finding is in line with the initial immunological analysis we have performed on the separate controlled human infection studies( 3, 5 ), as well as a recent murine study which found no immunological differences in chronic male or female single-sex infection( 48 ). However, it is still surprising in the context of prior papers that have shown sex-related differences in immune priming, as well as the known morphological and transcriptional differences between male and female worms ( 4952 ).…”
Section: Discussionsupporting
confidence: 88%
“…Throughout infection, we have shown only minor differences in immune response between female and male single-sex infections. This finding is in line with the initial immunological analysis we have performed on the separate controlled human infection studies ( 3 , 5 ) and a recent murine study that found no immunological differences in chronic male or female single-sex infection ( 14 ). However, it is still unexpected in the context of prior papers that have shown sex-related differences in immune priming, as well as the known morphological and transcriptional differences between male and female worms ( 15 18 ).…”
Section: Discussionsupporting
confidence: 88%
“…In murine models, egg production is the major driver of type 2 immune responses in schistosomiasis (10), with a mixed type 1/type 2 response present in prepatent or single-sex S. mansoni infection (11)(12)(13). Schistosome worms exhibit marked morphological and transcriptional differences dependent on sex; however, whether this translates to altered immune phenotypes is unclear (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“… 17 The similarity between male- and female-induced immune responses is in line with recent work using long-term male and female schistosome infections in a murine model. 18 However, it contrasts prior literature which suggested male-only infections induce a more pro-inflammatory response, whilst female-only infection are characterized by more regulatory profiles. 7 , 19 However, given the very small set of individuals in both our male- and female-only CHI-S studies, more in-depth immunological assessments will be needed to confirm similarity of immune interaction between male and female worms.…”
Section: Discussionmentioning
confidence: 77%